Balancing convenience and risk: Personality traits, buy now pay later usage, and consumer well-being - Dewi Khornida Marheni; Rhukil Cahyani Amalia; Yulfiswandi Yulfiswandi; Hanini Ilyana Che Hashim (Jurnal Fokus Manajemen Bisnis, 2026)
A convenience that comes with the rapid expansion of buy now, pay later use also increases the risk of impulsive spending and debt. This research aims to examine how consumer personality traits, such as mindfulness, impulse-buying tendency, and pain of payment, influence buy now pay later use and affect the financial and psychological well-being of Generation X, Y, and Z in Indonesia. To conduct the quantitative portion of the study, a purposive sampling approach was used to survey 473 Indonesians from Generations X, Y, and Z who have experience with buy now, pay later services. A structural equation model using a partial least squares-structured equation model with SmartPLS. The results indicate that mindfulness is more likely to be used now, with pay later, and that this behavior is guided by greater intention and planning, as shown by a favorable and substantial direct influence of mindfulness on this behavior. However, the association between mindfulness and buy now, pay later is not substantially mediated by impulsivity or financial self-control. Pain of payment is found to positively moderate the correlation between impulse buying tendency and buy now, pay later, thereby strengthening the effect under certain payment conditions. Furthermore, overall well-being is directly and positively impacted by buy now, pay later. However, anticipated future financial security does not affect overall well-being. Nevertheless, buy now, pay later indirectly affects overall well-being through current money management stress. Understanding psychological factors that impact digital financial behavior and its offerings provides important recommendations for regulators and buy-now-pay-later providers, including the need for financial stress management, service transparency, and consumer protection.